2013
DOI: 10.1177/193229681300700403
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Performance of a Novel System for Continuous Glucose Monitoring

Abstract: Abbreviations: (BG)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
48
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(51 citation statements)
references
References 22 publications
(42 reference statements)
2
48
0
Order By: Relevance
“…Since it is only recently that any devices have even approached such performance, regulatory criteria for device approval have been more pragmatic, focusing on the hazards of incorrect readings (e.g., suboptimal treatment decisions, including improper adjustments in medication dosage, potentially increasing the frequency of both hypoglycemia and hyperglycemia) (58). Accuracy, ergonomics, and ease of use of blood glucose meters have improved dramatically over time (124)(125)(126), and the accuracy of CGM is beginning to approach that of BGM devices (113,114,(127)(128)(129)(130). However, a clinically significant variation in accuracy and precision persists among currently marketed GM devices.…”
Section: Gm Accuracy Precision and Data Display Metricsmentioning
confidence: 99%
“…Since it is only recently that any devices have even approached such performance, regulatory criteria for device approval have been more pragmatic, focusing on the hazards of incorrect readings (e.g., suboptimal treatment decisions, including improper adjustments in medication dosage, potentially increasing the frequency of both hypoglycemia and hyperglycemia) (58). Accuracy, ergonomics, and ease of use of blood glucose meters have improved dramatically over time (124)(125)(126), and the accuracy of CGM is beginning to approach that of BGM devices (113,114,(127)(128)(129)(130). However, a clinically significant variation in accuracy and precision persists among currently marketed GM devices.…”
Section: Gm Accuracy Precision and Data Display Metricsmentioning
confidence: 99%
“…8,20 In total, there were 30 subjects who wore system B sensors; 20 10 of these subjects also wore system A sensors. 8 Detailed information about the study procedure and participants can be found in the respective publications.…”
Section: Study Design and Populationmentioning
confidence: 99%
“…8 Detailed information about the study procedure and participants can be found in the respective publications. 8,20 The analysis presented here is based on data of the 10 subjects who wore both systems in parallel. Each of these subjects wore 2 sensors of each system type simultaneously.…”
Section: Study Design and Populationmentioning
confidence: 99%
See 1 more Smart Citation
“…Unlike the consistent results observed with the Roche prototype sensor, the other systems tested either showed modest overall performances or lacked sufficient accuracy at clinically relevant times, namely, critical periods of hypoglycemia or when the BG level is changing rapidly. 15 Looking into the future, Schoemaker predicted that, one day, CGM technology will become a routine part of personalized diabetes management, and he is convinced of the expanding role and clinical significance of CGM systems. Enhanced accuracy and generation of clinically actionable CGM data are key features to ensure future success of CGM technology, Schoemaker contended.…”
Section: An Accurate Sensor In the Makingmentioning
confidence: 99%